Negotiating Power Relations of African-American Women Musicians in the Jazz Scene of the 1920’s to the 1960’s - Andi Alexander (Repertoar, 2026)
African-American women whose jazz musicians constitute a double minority, facing gender and racial discrimination in their creative process. Social conditions from the 1920s to the 1960s were heavily dominated by masculinity and the European-American majority, which dictated existing social values. This study aims to uncover the struggles of African-American women jazz musicians to negotiate the social, cultural, and political structures that limited their participation in the jazz music scene, based on Bourdieu's field of struggle perspective and various gender theories. The research method uses a qualitative approach through a literature review utilizing various written historical sources. The results show that African-American women jazz musicians were able to build significant positions and contributions through social, symbolic, and cultural capital both in musical practice and within community networks. The presence of alternative spaces such as jam sessions, churches, and community groups became important means for the exchange of knowledge and the formation of solidarity among African-American women jazz musicians. Further research could delve deeper into the negotiation of power relsations between women jazz musicians who constitute a double minority in other regions and eras.